PROSES BERPIKIR SISWA KELAS V SEKOLAH DASAR DALAM MEMECAHKAN MASALAH MATEMATIKA - Sudibyo, Nugroho Arif; Budiyono, Budiyono; Sujadi, Imam (Jurnal Pembelajaran Matematika, 2014)
Abstract: This study aim to describe the thinking process of elementary school fifth grade students in solving mathematics problem based on Krulik and Rudnick rule. This research was a qualitative research using the case study method. Sampling was done by a combination of purposive sampling and snowball sampling technique. The subject of research that used in this study was twelve subjects, that was: four high-ability students, four moderate-ability students and four low-ability students. The data was validated by using a time triangulation test. The results show: (1) At the step of reading and thinking, students do not directly identify all of the facts in writing. After identifying the facts, students identify questions from the given problem. Furthermore, students do not portray the problems encountered but directly process the needed information to answer the question; (2) At the step of exploring and planning, students organize the information on the matter. Students consider enough information on the matter because there is a relation between the known and the asked. On the other hand, students do not make tables, diagrams, charts, tables or images from a given problem, but directly chose a strategy to answer the question; (3) At the step of selecting the strategy, students use the making list of all possible answers strategy. Students write down all the possibilities answers in the answer sheet. However, there are students who also use the guessing and testing strategy, guess how the value of variable and test whether the variable value is correct. In addition there are also students who use simulation or experimental strategies, students try to experiments; (4) At the step of finding the answer, the student use estimation in finding the answer. On the other hand, there is one student who uses algebra ability to find the answers. Students are also assuming the third day as a variable. After obtaining the value of the variable, student examine whether the numbers are correct. (5) At the step of reflecting and extending, students can review the results of the calculation by return on the answer sheet. Then students find that the answer is correct. Furthermore, students assume no alternative other solutions. Then the students do not make a generalizations of matter and discover the concept of matter.Keywords: process thinking, mathematics and problem solving.